Surviving the Covid-19 Pandemic: Analysis of the Grit Factor in Students - Septania, Sovi; Sulastri, Sulastri (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2020)
Covid-19 pandemic had a massive impact to all aspects in society, including university students. Challenge of online study and family’s economic pressure forced them to turn this situation into strategy to survive amid several limitations. This strategy known as grit. Grit is a psychological contruct which first introduced by Duckworth (2007). Its definition is expanding through the years, but it keeps referring to its initial definition as perseverance and willingness to achieve long-term goals. Grit scale consist of 16 items with two main aspects, consistency in interest and perseverance in action. Purpose of this study was to analyze which factors in grit which mostly impact to survival strategy in students. This research involved 318 university students using purposive sampling method. Data which have been collected was categorized into five main factors which relate to students’s survival strategy consist of consitency, efforts to maintain goals, encounter challenges, executing task and hardwork. Final result using factor analysis with the help of SPSS 25.0 program, showed that those factor reduce into two main factor consist of goal clarity and persistency.